Saving the Environment: Environmental Lessons in Colin Thiele’s February Dragon - Arafah, Burhanuddin; Abbas, Herawaty; Hikmah, Nurul (Journal of language teaching and research, 2021)
This article explores the relationship between humans and nature in February Dragon and elaborates on the environmental lessons conveyed in Colin Thiele's February Dragon. This article utilizes the concept of ecocriticism by Glotfelty. Ecocriticism explains human-nature interconnectedness. The portrayal of human-nature relation reveals several values of environmental education that readers, both children, and adults, could learn. Three environmental lessons such as respect, responsibility, and empathy towards other living beings were found in the story. Based on the elaborations, the characters in the novel show their respect, responsibility, and empathy towards other species by protecting the animal and the environment from bushfire’s dangers.